ROLE OF MAGNETIC RESONANCE AND PET CT IN DETECTION OF HEPATAL METASTASIS - Prgova Veljanova, Biljana; Bozinovska, Biljana; Kostova, Masha; Bozinovska, Teodora; Bozinovska- Beaka, Gordana; Veljanovski, Dimitar (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Metastatic spread of primary tumours is best detected by various radiological methods such as ultrasound, CT, MRI as well as PET CT the latest MRI/PET. The benefit of various types of liver metastasectomies and the use of radiofrequency ablation of lesions in patients with various cancers . The objective of our study is to assess the relative performance of different radiology methods, magnetic resonance (MR) and 18FDG positron emission computed tomography (PET CT) and to emphasize superiority of one of them with a goal of better planning of oncology and surgery treatment of patients with metastasis of liver smaller than 10 mm. Imaging data of 70 patients in 4 years, enhanced liver MRI and whole-body FDG PET CT were reviewed for the presence and number of liver metastases In comparison to the FDG PET CT, the MRI detected all hepatic metastases. All lesions were identified on MRI (420), whereas only 296 were detected on FDG PET. 91 of them with diameter less than 10mm were detected only on MRI .FDG PET CT provided additional information about extrahepatic disease and was useful in initial staging. However, significantly more and smaller than 10 mm liver metastases were detected on MRI than on FDG PET. MRI has presented more information concerning peripheral ring and PET CT is accurate for identification of metabolic activity of hepatic metastases greater than 10mm in diameter Both complementary methods give correct pathways in treatment and in building of criteria for appropriate liver metastasectomies and radio-frequent ablations. Key words: metastasis, liver, MR, PET CT , 18FDG